NEONATE OUTCOME AND RESPONSE TIME FOR EMERGENCY CESAREAN SECTION : A SCOPING REVIEW - Diah Melly Marlyana; Atik Nurwahyuni; Adik Wibowo (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Emergency CS response time guidelines by the National Institute for Health Care Excellence (NICE) were difficult to implement in many countries, and these constraints have led to poor neonate outcomes in several previous studies. The purpose of this study is to determine the affordability of emergency CS response time based on NICE recommendations, as well as its correlation to neonatal outcome in lower-middle income countries, as well as response time-related factors. This scoping review data was extracted from several electronic data bases, which were accessed in February–March 2022, applying the PRISMA–ScR approach. Six eligible studies that meet inclusion criteria from 4,102 articles were obtained and analyzed. The average DDI achievement percentage remained less than 20%, and worse neonate outcomes were not significantly related to delayed response time. Factors related to delayed response times need to be corrected.